Preparation method and application of nitrogen-vacancy-rich Co carbon-loaded catalyst wrapped by amorphous carbon layer

By developing nitrogen-rich vacancies Co-carrying carbon catalysts wrapped with amorphous carbon layer, the problems of single application, complex preparation and poor stability of existing catalysts are solved, and a catalytic effect with high efficiency, stability and multifunctionality in the molecular selective hydrogenation reaction of biomass platform is achieved.

CN119588395APending Publication Date: 2025-03-11XIANGTAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411778743.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-25
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing catalysts are single-use in molecular selective hydrogenation reactions on biomass platform, the preparation process is complex and costly, and poor stability is difficult to achieve multifunctional catalytic effect.

Method used

A nitrogen-rich vacancies Co-carrying carbon catalyst wrapped with an amorphous carbon layer was developed to obtain nitrogen-rich vacancies C3N4 powder by pyrolysis of melamine, thiourea, urea, etc., and stir with glucose and soluble cobalt salt in an aqueous solution to form a mixed solution. After low-temperature water heat treatment, carbon thermal reduction under a nitrogen atmosphere was obtained to obtain a catalyst.

Benefits of technology

This catalyst exhibits high activity, high stability and high selectivity in multiple selective hydrogenation reactions such as levulinic acid, nitrobenzene, furfural, etc. The catalyst preparation process is simple and has broad market prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588395A_ABST
    Figure CN119588395A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a nitrogen-rich vacancy Co carbon-loaded catalyst wrapped by an amorphous carbon layer. The preparation method comprises the following steps: step 1, pyrolyzing at least one of melamine, thiourea, urea and dicyandiamide in a nitrogen atmosphere to obtain nitrogen-rich vacancy C3N4 powder; 2, mixing the C3N4 powder with glucose and soluble Co salt in an aqueous solution, putting the mixture into a polytetrafluoroethylene-lined reaction kettle, performing low-temperature hydrothermal treatment, and performing centrifugal filtration and drying to obtain a catalyst precursor; 3, the precursor is subjected to carbon thermal reduction at the temperature of 500-800 DEG C in the nitrogen atmosphere, and the catalyst is obtained. The catalyst provided by the invention has the advantages of simple preparation process, low cost, high catalyst yield, high specific surface area of 320m < 2 > / g, magnetic property, easiness in recycling and the like. The catalyst has relatively high activity and selectivity on multiple catalytic hydrogenation reactions of aromatic nitro compounds, levulinic acid, furfural and the like, and has the advantages of mild reaction conditions, high cycle stability, no metal leaching and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogenation catalysts, and specifically relates to a preparation method of a nitrogen vacancy-rich Co-supported carbonaceous catalyst wrapped in an amorphous carbon layer and its application in the selective hydrogenation of nitro compounds, levulinic acid, furfural and the like. Background Art

[0002] Biomass energy has great potential in replacing traditional fossil fuels and adjusting the energy structure, and is expected to achieve the goal of sustainable energy supply. Biomass chemical components include cellulose, hemicellulose and lignin. Based on thermochemical processes such as gasification, pyrolysis and liquefaction, lignocellulose can be converted into synthesis gas and bio-oil, and can be converted into aromatic compounds of different components, gasoline-grade hydrocarbon fuels and additives through post-processing. Cellulose and hemicellulose can be dehydrated to obtain furfural, 5-hydroxymethylfurfural, levulinic acid, etc. after hydrolysis, but these compounds contain multiple functional groups (such as aldehyde, hydroxyl, carboxyl and carbon-carbon double bonds, etc.), which may cause competitive reactions to generate by-products during catalytic conversion. Therefore, choosing a suitable catalytic system to guide the reaction substrate to transform in the direction of a specific product is a key step in obtaining a single chemical.

[0003] The selective hydrogenation process based on biomass platform molecules plays an important role in the production of fine chemicals and their downstream products. For example, both levulinic acid (LA) and γ-valerolactone (GVL) can be converted into high value-added chemicals, materials and liquid fuels. The selective hydrogenation of LA is the main strategy for the synthesis of GVL. The catalytic hydrogenation of aromatic nitro compounds can prepare aniline compounds. Aniline, as an important basic chemical raw material, is widely used in the pharmaceutical, dye and rubber industries. About 85% of aniline in the world is obtained by hydrogenation of nitrobenzene. Furfural is a product of lignocellulose hydrolysis. Furfuryl alcohol, as a derivative of furfural, has been widely used in agriculture, printing and industry. The selective hydrogenation of furfural is the main process for the synthesis of furfuryl alcohol in industrial production. However, under normal conditions, the aldehyde functional group in the furfural structure is less active than the unsaturated carbon-carbon double bond, and it is usually preferentially hydrogenated to form furan compounds. Obviously, the development of a class of highly active, highly selective and highly stable catalysts is crucial for the selective hydrogenation of biomass platform molecules.

[0004] Chinese patent CN114308094B discloses a method for preparing cobalt single atom / nitrogen doped mesoporous carbon fiber. First, zinc and cobalt salt are dissolved in an organic solvent to obtain solution A, and trimesic acid is dissolved in an organic solvent to obtain solution B; A and B are mixed to carry out a solvent thermal reaction to generate cobalt-zinc trimesic acid fiber; the cobalt-zinc trimesic acid fiber is pyrolyzed under an inert atmosphere and then hydrogen reduced to obtain a catalyst. The catalyst can achieve complete conversion of levulinic acid, and the yield of γ-valerolactone reaches 95%. After the catalyst is repeated 5 times, the yield of γ-valerolactone is still higher than 80%. The literature (J. Catal., 2017, 348: 212-222) reported the synthesis of Co-embedded nitrogen-doped mesoporous carbon catalysts based on cobalt phthalocyanine precursors and SiO2 templates through pyrolysis and de-templating processes. The catalyst Co@NMC-800 (2 mol% Co) has excellent activity and selectivity for hydrogenation of various nitroaromatics to prepare aniline compounds within 150 min at 80°C and 1.0 MPa hydrogen pressure. The literature (Mol. Catal., 2024, 553: 113752) reported the preparation of C3N4 by pyrolysis of urea as a raw material, impregnation of cobalt nitrate and ultrasonication to form a composite precursor, and then calcination at 280°C and 450°C in two stages to obtain a nitrogen-doped carbon-coated cobalt catalyst Co-NC-450. The catalyst can achieve complete conversion of furfural and a furfuryl alcohol yield of 100% when reacted at 110°C and 1.5 MPa hydrogen pressure for more than 2 hours. The above cases fully demonstrate that Co-loaded nitrogen-doped carbon materials have excellent activity in the selective hydrogenation of various biomass platform molecules, and can effectively solve the problem of low catalytic activity and poor selectivity of other types of catalysts in different reactions.

[0005] The existing technology shows that the catalyst is relatively single and specific in the application of selective hydrogenation. The same catalyst has great limitations in realizing multiple catalytic hydrogenation applications simultaneously during the production process. It is a great challenge to develop a multifunctional catalyst with high catalytic activity and high stability. C3N4 with rich nitrogen vacancies is a type of electron-rich material. The high-density nitrogen atom structure can firmly capture metals and significantly increase the electron cloud density of metal active sites. As a catalyst, it can effectively enhance the catalytic activity. In theory, when C3N4 is co-pyrolyzed with a metal source to form a supported carbon catalyst, nitrogen-rich vacancies will be introduced simultaneously, resulting in a large number of lattice defects in the six-membered ring structure of the carbon layer. This structural feature can provide more transmission channels and metal ion storage active sites for rapid ion diffusion. In addition, most catalysts are prone to metal agglomeration or leaching during the cycle, and the catalytic activity drops sharply after multiple cycles. The use of metal encapsulation strategy can solve the problem of metal agglomeration and escape to a certain extent, but most encapsulated catalysts require the use of a large amount of template agents, and the reaction process is complicated and there is environmental pollution. Therefore, it is urgent to provide an environmentally friendly, highly active, qualitatively high and low-cost multifunctional catalyst. Summary of the invention

[0006] The purpose of the present invention is to develop a multifunctional catalyst to solve the problems in the prior art regarding the single application of catalysts, complex preparation process, high cost and poor stability in the selective hydrogenation reaction of biomass platform molecules.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a nitrogen-rich vacancy Co-supported carbon catalyst wrapped in an amorphous carbon layer, which is applied to multiple selective hydrogenation reactions such as levulinic acid, nitrobenzene, furfural, etc. under the conditions of reaction solvent and certain hydrogen pressure and temperature, and shows the characteristics of high activity, high stability and high selectivity. The catalyst preparation process is simple and has extremely broad market prospects.

[0008] The preparation method and application of the nitrogen-rich vacancy Co-supported carbon catalyst wrapped by an amorphous carbon layer specifically include the following steps:

[0009] (1) thermally decomposing at least one of melamine, thiourea, urea and dicyandiamide to obtain nitrogen vacancy-rich C3N4 powder;

[0010] (2) the C3N4 obtained in step (1), glucose and soluble cobalt salt are fully stirred in an aqueous solution in a certain weight ratio to form a mixed solution, the solution is placed in a polytetrafluoroethylene-lined reactor for low-temperature hydrothermal treatment, cooled to room temperature, centrifuged and filtered to dry to obtain a catalyst precursor;

[0011] (3) Carbothermally reducing the catalyst precursor obtained in step (2) under a nitrogen atmosphere to obtain the catalyst.

[0012] As a preferred embodiment, the pyrolysis atmosphere in step (1) is nitrogen, the pyrolysis temperature is 500°C to 600°C, preferably 550°C; the reaction time is 2 to 6 hours, preferably 4 hours; and the heating rate is 5°C / min.

[0013] As a preferred embodiment, the soluble cobalt salt in step (2) is at least one of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt sulfate heptahydrate and cobalt chloride hexahydrate.

[0014] As a preferred embodiment, the mass ratio of glucose to C3N4 in step (2) is 1: (0.2-1), and the mass ratio of soluble cobalt salt to C3N4 is 1: 1. The hydrothermal reaction temperature is 140-180°C, preferably 170°C; the hydrothermal reaction time is 6-36h, preferably 24h.

[0015] As a preferred embodiment, the carbon thermal reduction temperature in step (3) is 500-800°C, preferably 600°C; the reaction time is 1-3h, preferably 2h; and the heating rate is 3°C / min.

[0016] The invention discloses an application of a Co-supported carbon catalyst rich in nitrogen vacancies wrapped in an amorphous carbon layer in the selective hydrogenation reaction of aromatic nitro compounds, levulinic acid and furfural, characterized in that the catalyst, a solvent and a reaction substrate are contacted in a closed polytetrafluoroethylene reactor lining, hydrogen is used as a hydrogen source, the hydrogen pressure is 0.6 to 2 MPa, the reaction temperature is 60 to 200°C, and the reaction time is 2 to 4 hours; the solvent is one of 1,4-dioxane, isopropanol, methanol and ethanol.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The catalyst preparation process provided by the present invention is simple, the conditions are easy to control, and large-scale production can be achieved. The C3N4 component in the catalyst can enhance the Co electron cloud density, and can also self-reduced to produce low-valent Co anchor active sites and increase dispersion; glucose can form an amorphous carbon layer to wrap the metal particles, inhibiting their leaching during the reaction; the two work together to make the catalyst exhibit a multifunctional catalytic effect, and can achieve a mild, efficient, and highly selective hydrogenation process in multiple biomass platform molecules such as levulinic acid, furfural, and nitrobenzene;

[0019] (2) The catalyst provided by the present invention has high reaction efficiency, good stability, and can be used for a long time. In particular, in the hydrogenation reaction of levulinic acid and nitrobenzene, complete conversion can be achieved even after 10 repeated uses, and the selectivity of the target products γ-valerolactone and aniline is still as high as 98%, which has important industrial application value in the field of fine chemical production.

[0020] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the nitrogen adsorption isotherm and pore size distribution diagram of the catalyst described in Example 1.

[0022] Figure 2 It is the nitrogen adsorption isotherm and pore size distribution diagram of the catalyst described in Comparative Example 1.

[0023] Figure 3 The change of the catalyst described in Example 1 in the hydrogenation of levulinic acid in Application Example 1 with the reaction time.

[0024] Figure 4 The change of the catalyst described in Example 1 in nitrobenzene hydrogenation in Application Example 2 with reaction time.

[0025] Figure 5 The change of furfural hydrogenation with the catalyst described in Example 4 in Application Example 3 as a function of reaction time. DETAILED DESCRIPTION

[0026] In order to further disclose but not limit the present invention, the present invention is further described in detail below with reference to examples.

[0027] Embodiment 1:

[0028] The crucible of melamine was placed in a tubular furnace, and nitrogen was introduced to pyrolyze at 550°C for 4 hours (heating rate 5°C / min). After cooling to room temperature, it was ground to obtain yellow C3N4 powder. 0.6g of the C3N4 powder, 1g of glucose and 0.6g of cobalt nitrate hexahydrate were weighed and added to 60mL of pure water and stirred for 30 minutes. Then, the mixture was transferred to a polytetrafluoroethylene reactor and hydrothermally treated at 170°C for 24 hours. After the reaction, it was naturally cooled to room temperature. The solid product was repeatedly washed with deionized water until it was neutral and dried at 80°C for 12 hours. The obtained sample was then pyrolyzed at 600°C in a nitrogen atmosphere for 2 hours (heating rate 3°C / min). After naturally cooling to room temperature, it was taken out to obtain a nitrogen-rich Co-supported carbon catalyst wrapped in an amorphous carbon layer. The catalyst was named Co@NC-01. By Figure 1 It can be seen that the nitrogen adsorption isotherm of the catalyst has an obvious hysteresis loop at a relative pressure of 0.45-1.0, and the pore size distribution shows that the catalyst is rich in mesopores of 10-50 nm and has a specific surface area of ​​303 m 2 / g.

[0029] Embodiment 2:

[0030] The steps are the same as those in Example 1, except that melamine, a precursor for preparing C3N4, is replaced by thiourea. The other steps are the same as those in Example 1, and the catalyst is named Co@NC-02.

[0031] Embodiment 3:

[0032] The steps are the same as those in Example 1, except that melamine, a precursor for preparing C3N4, is replaced by urea. The other steps are the same as those in Example 1, and the catalyst is named Co@NC-03.

[0033] Embodiment 4:

[0034] The steps are the same as those in Example 1, except that the precursor melamine for preparing C3N4 is replaced by a mixture of melamine and thiourea. The other steps are the same as those in Example 1, and the catalyst is named Co@NC-12. Figure 2 It can be seen that the nitrogen adsorption isotherm of the catalyst has an obvious hysteresis loop at a relative pressure of 0.8-1.0, and the pore size distribution shows that the catalyst is rich in mesopores of 30-50 nm and has a specific surface area of ​​240 m 2 / g.

[0035] Specific application

[0036] In order to further disclose but not limit the present invention, the present invention is further described in detail below in combination with application examples. Application Example 1:

[0037] This application example is used to illustrate the reaction of efficiently catalyzing the conversion of levulinic acid to γ-valerolactone using the nitrogen-vacancy-rich Co-supported carbon catalyst wrapped with the amorphous carbon layer described in Examples 1 to 4.

[0038] Weigh 0.05g of the catalyst described in Examples 1 to 4, 0.5g of levulinic acid and 20mL of 1,4-dioxane and add them to a 50mL polytetrafluoroethylene high-pressure reactor, and introduce high-purity hydrogen five times to replace the air in the reactor. Then close the valve, introduce hydrogen to adjust the pressure to 1.8MPa and stabilize it. When the reaction temperature approaches the set temperature of 180°C, turn on the magnetic stirrer switch and react at a speed of 1000rpm / min for 3h. After the reaction is completed, naturally cool to room temperature and take samples to analyze the catalytic performance by gas chromatography. The test results are shown in Table 1. The analysis results show that under appropriate reaction parameters, the catalyst Co@NC-01 described in Example 1 can achieve complete conversion of levulinic acid, and the selectivity of γ-valerolactone is greater than 99.7%. The specific relationship between the catalytic activity and the reaction time is as follows: Figure 3 shown.

[0039] Table 1 Selective hydrogenation performance of levulinic acid of the catalysts described in Examples 1 to 4 (solvent is 1,4-dioxane)

[0040]

[0041] Application Example 2:

[0042] This application example is used to illustrate the reaction of efficiently catalyzing the conversion of nitrobenzene to aniline using the nitrogen-vacancy-rich Co-supported carbon catalyst wrapped by the amorphous carbon layer described in Examples 1 to 4.

[0043] Weigh 0.05g of the catalyst described in Examples 1 to 4, 0.25g of nitrobenzene and 20mL of ethanol and add them to a 50mL polytetrafluoroethylene high-pressure reactor. The specific selective hydrogenation method steps are the same as those in Application Example 1. The reaction parameters are appropriately adjusted, the hydrogen pressure is 0.6MPa, the reaction temperature is set to 100°C, and the reaction time is changed to 2h. After the reaction is completed, gas chromatography is used to detect the efficiency of the catalyst in the selective hydrogenation of nitrobenzene to prepare aniline. The test results are shown in Table 2. The analysis results show that under appropriate reaction parameters, the catalysts Co@NC-01 and Co@NC-12 described in Examples 1 and 4 can achieve complete conversion of nitrobenzene, and the selectivity of aniline is greater than 99.9%. The specific relationship between the catalytic activity of the catalyst Co@NC-01 described in Example 1 in the preparation of aniline from nitrobenzene and the reaction time is as follows Figure 4 shown.

[0044] Table 2 Nitrobenzene selective hydrogenation performance of the catalysts described in Examples 1 to 4 (solvent is ethanol)

[0045]

[0046] Application Example 3:

[0047] This application example is used to illustrate the reaction of efficiently catalyzing the conversion of furfural to furfuryl alcohol using the nitrogen-vacancy-rich Co-supported carbon catalyst wrapped with the amorphous carbon layer described in Examples 1 to 4.

[0048] Weigh 0.05g of the catalyst described in Examples 1 to 4, 0.25g of furfural and 20mL of isopropanol and add them to a 50mL polytetrafluoroethylene high-pressure reactor. The specific steps of the selective hydrogenation method are the same as those in Application Example 1. The reaction parameters are appropriately adjusted, the hydrogen pressure is 1.2MPa, the reaction temperature is set to 120°C, and the reaction time is 3h. After the reaction is completed, gas chromatography is used to detect the efficiency of the catalyst in the selective hydrogenation of furfural to prepare furfuryl alcohol. The test results are shown in Table 3. The analysis results show that under appropriate reaction parameters, the furfural conversion rate of the catalyst Co@NC-12 described in Example 4 is 99.1%, and the selectivity of furfuryl alcohol is greater than 96.2%. The specific relationship between its catalytic activity and reaction time is as shown in Figure 5 shown.

[0049] Table 3 Furfural selective hydrogenation performance results of the catalysts described in Examples 1 to 4 (solvent is isopropanol)

[0050]

[0051] Application example 4:

[0052] This application example is used to illustrate the reaction of efficiently catalyzing the conversion of p-chloronitrobenzene to p-chloroaniline using the nitrogen vacancy-rich Co-supported carbon catalyst wrapped by the amorphous carbon layer described in Examples 1 to 4.

[0053] 0.05 g of the catalyst described in Examples 1 to 4, 0.25 g of p-chloronitrobenzene and 20 mL of ethanol were weighed and added to a 50 mL polytetrafluoroethylene high-pressure reactor. The specific selective hydrogenation method steps were the same as those in Application Example 1. The reaction parameters were adjusted appropriately, the hydrogen pressure was set to 1.0 MPa, the reaction temperature was set to 80°C, and the reaction time was 3 h. After the reaction was completed, the efficiency of the catalyst in the selective hydrogenation of p-chloronitrobenzene to prepare p-chloroaniline was detected by gas chromatography, and the test results are shown in Table 4. The analysis results show that under appropriate reaction parameters, the conversion rate of p-chloronitrobenzene obtained by the catalyst Co@NC-01 described in Example 1 is 99.9%, and the selectivity of p-chloroaniline is greater than 95.1%.

[0054] Table 4 Selective hydrogenation performance of p-chloronitrobenzene of the catalysts described in Examples 1 to 4 (solvent is ethanol)

[0055]

[0056] In order to verify the effectiveness of the amorphous carbon layer wrapping strategy in enhancing catalytic activity, reducing the escape of metal active sites, and enhancing catalyst stability, the nitrogen-rich vacancy Co-supported carbon catalysts wrapped with amorphous carbon layers described in Examples 1 to 4 were tested for stability under optimal conditions using Examples 1 to 3. The results of 10 repeated tests showed that the catalyst had excellent stability. The selectivity of γ-valerolactone and aniline of the catalyst Co@NC-01 described in Example 1 remained above 98% after 10 cycles of testing; the selectivity of furfuryl alcohol of the catalyst Co@NC-12 described in Example 4 was still greater than 95% after 10 cycles of use, and the selectivity of p-chloroaniline was greater than 90%.

[0057] Comparative Example 1:

[0058] As in Example 1, a crucible of melamine was placed in a tubular furnace, and nitrogen was introduced to pyrolyze at 550°C for 4 h (heating rate 5°C / min). After cooling to room temperature, the mixture was ground to obtain yellow C3N4 powder.

[0059] Weigh 0.6 g of the C3N4 powder and 0.6 g of cobalt nitrate hexahydrate, add them into 60 mL of pure water, stir for 30 min, transfer them into a polytetrafluoroethylene reactor, perform hydrothermal treatment at 170° C. for 24 h, cool naturally to room temperature after the reaction, wash the solid repeatedly with deionized water until it is neutral, and dry at 80° C. for 12 h.

[0060] The solid was pyrolyzed at 600 °C in a nitrogen atmosphere for 2 h (heating rate 3 °C / min), and then naturally cooled to room temperature to obtain a nitrogen-rich Co-supported carbon catalyst named Co-NC-00 with a specific surface area of ​​228 m 2 / g.

[0061] The catalyst Co-NC-00 described in comparative example 1 is used for selective hydrogenation of levulinic acid, nitrobenzene, furfural and p-chloronitrobenzene, respectively, characterized in that the application method is the same as the method described in application examples 1 to 4, and under the optimal conditions of the method described in application examples 1 to 4, the conversion rates of levulinic acid, nitrobenzene, furfural and p-chloronitrobenzene are 84.5%, 99.9%, 64.5% and 91.2% respectively; the selectivity of the target products γ-valerolactone, aniline, furfuryl alcohol and p-chloroaniline are 92.2%, 99.9%, 45.6% and 60.2% respectively. The performance comparison results with the catalyst described in examples 1 to 4 fully confirm that the strategy of glucose wrapping in the formation of an amorphous carbon layer is very beneficial to improving the activity and stability of the catalyst, because the amorphous carbon layer wrapping can further disperse the active metal and inhibit the leaching of the active metal particles in the reaction solution.

[0062] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-rich vacancy Co-supported carbon catalyst wrapped in an amorphous carbon layer and its application, characterized in that: Using hydrogen as the hydrogen source, it is suitable for hydrogenation applications of multiple reaction substrates such as aromatic nitro compounds, levulinic acid and furfural; The hydrogen pressure is 0.6-2MPa, the reaction temperature is 60-200°C, and the reaction time is 2-4h; The Co content in the catalyst is 0.4-6.4 wt% and is wrapped in the amorphous carbon layer in the form of nanoparticles. The particle size is 10-40 nm. The catalyst is rich in mesopores and has a specific surface area of ​​50-360 m 2 / g; The preparation method of the amorphous carbon-wrapped nitrogen-rich vacancy Co-supported carbon catalyst comprises the following steps: Step 1: pyrolyzing at least one of melamine, thiourea, urea and dicyandiamide under a nitrogen atmosphere to obtain C3N4 rich in nitrogen vacancies; Step 2: Fully stir the C3N4 obtained in step 1, glucose and soluble cobalt salt in an aqueous solution according to a certain weight ratio, place the mixed solution in a polytetrafluoroethylene-lined reactor for one-step hydrothermal treatment, cool to room temperature, centrifuge and filter to dry to obtain a catalyst precursor; Step 3: Carbothermally reduce the catalyst precursor obtained in step 2 under a nitrogen atmosphere to obtain a nitrogen-rich Co-supported carbon catalyst wrapped in an amorphous carbon layer.

2. The method for preparing a catalyst according to claim 1, characterized in that: The reaction temperature for preparing C3N4 by pyrolysis in step 1 is 500-600°C, preferably 550°C; the reaction time is 2-6h, preferably 4h, and the heating rate is 5°C / min.

3. The method for preparing a catalyst according to claim 1, characterized in that: The cobalt salt in step 2 is one of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt sulfate heptahydrate and cobalt chloride hexahydrate, preferably cobalt nitrate hexahydrate.

4. The method for preparing a catalyst according to claim 1, characterized in that: In step 2, the mass ratio of glucose to C3N4 is 1:(0.2-1), the mass ratio of soluble cobalt salt to C3N4 is 1:1, the hydrothermal reaction temperature is 140-180°C, preferably 170°C; the hydrothermal reaction time is 6-36h, preferably 24h.

5. The method for preparing a catalyst according to any one of claims 1 to 4, characterized in that: In step 3, the carbon thermal reduction temperature is 500-800°C, preferably 600°C, and the heating rate is 3°C / min; the reaction time is 1-3h, preferably 2h.

6. Use of a Co-supported carbon catalyst rich in nitrogen vacancies wrapped in an amorphous carbon layer obtained by the method according to any one of claims 1 to 5 in the selective hydrogenation reaction of aromatic nitro compounds, levulinic acid and furfural.

7. The catalyst obtained according to any one of claims 1 to 6, characterized in that The catalyst, solvent and reaction substrate are contacted in a closed polytetrafluoroethylene reactor lining, hydrogen is used as the hydrogen source, the pressure is 0.6-2MPa, the reaction temperature is 60-200°C, and the reaction time is 2-4h; the solvent is one of 1,4-dioxane, isopropanol, methanol and ethanol.

Citation Information

Patent Citations

  • Cobalt single-atom / nitrogen-doped mesoporous carbon fiber materials, their preparation methods and applications

    CN114308094B